2019
DOI: 10.1261/rna.070193.118
|View full text |Cite
|
Sign up to set email alerts
|

PTBP1 mRNA isoforms and regulation of their translation

Abstract: Polypyrimidine tract-binding proteins (PTBPs) are RNA binding proteins that regulate a number of posttranscriptional events. Human PTBP1 transits between the nucleus and cytoplasm and is thought to regulate RNA processes in both. However, information about PTBP1 mRNA isoforms and regulation of PTPB1 expression remains incomplete. Here we mapped the major PTBP1 mRNA isoforms in HEK293T cells and identified alternative 5 ′ ′ ′ ′ ′ and 3 ′ ′ ′ ′ ′ untranslated regions (5 ′ ′ ′ ′ ′-UTRs, 3 ′ ′ ′ ′ ′-UTRs), as well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…For instance, eIF3 was found to bind PTBP1 mRNA isoforms in a cell-cycle-dependent manner. A strong correlation could be established between eIF3 binding to PTBP1 mRNAs and repression of PTBP1 expression during the S phase of the cell cycle (65). The translation of several additional mRNAs is repressed by eIF3.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, eIF3 was found to bind PTBP1 mRNA isoforms in a cell-cycle-dependent manner. A strong correlation could be established between eIF3 binding to PTBP1 mRNAs and repression of PTBP1 expression during the S phase of the cell cycle (65). The translation of several additional mRNAs is repressed by eIF3.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we found three genes, COL5A1, COL1A2, and CP with lengthened 3′ UTR were upregulated in tumors in both the datasets. Several genes have been reported that their longer 3′ UTR isoform can enhance expression through trans -regulation mechanism ( Allen et al, 2013 ; Arake et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…3). Given the RNA stabilization function of hnRNP I/L [19,20,36,37] and their combination with UCA1 (Fig. 2), it is likely that hnRNP I/L may affect metabolism at least partially through increasing the UCA1 stability, which explains the similar metabolic pro les.…”
Section: Discussionmentioning
confidence: 98%